2019
DOI: 10.1002/mus.26763
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring daily physical activity of upper extremity in young and adolescent boys with Duchenne muscular dystrophy: A pilot study

Abstract: Introduction Accelerometry of the upper extremity (UE) potentially provides information on the extent of activities in daily life in patients with Duchenne muscular dystrophy (DMD). The objective of this study is to evaluate the validity of home measurements of UE accelerometry. Methods This was a cross‐sectional study in 16 patients with DMD (aged 7‐17 years). Patients were monitored for 1 to 3 days with two accelerometers on the UE and one accelerometer on the wheelchair. Results The mean intensity of activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(38 citation statements)
references
References 33 publications
1
37
0
Order By: Relevance
“…In a recent study, Geest et al 2019found a strong correlation between movement data from accelerometers worn on the upper and lower arm of patients with DMD. They also suggest the use of a single wrist accelerometer to monitor physical activity in patients with DMD rather than two accelerometers [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, Geest et al 2019found a strong correlation between movement data from accelerometers worn on the upper and lower arm of patients with DMD. They also suggest the use of a single wrist accelerometer to monitor physical activity in patients with DMD rather than two accelerometers [13].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that in ambulatory patients with DMD, accelerometry detected physical activity increases after corticosteroid use, sensed the natural history of DMD, and it was strongly correlated with the 6 MWT [10][11][12]. In other studies, accelerometry data was strongly correlated with the Brooke Scale, DMDSAT, and PUL Scale in non-ambulatory patients [9,13]. In patients with DMD of differing ambulation status accelerometry was moderately and strongly correlated with the 6 MWT and QMT, respectively [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Measures of ambulatory activity such as the 6‐minute walk test (6MWT), climbing four stairs, and 10‐m walk/run are commonly used as clinical trial endpoints in school‐aged patients with DMD, even in whose who are in their wheelchairs most of the day. Upper limb activity might be an equally important outcome measure, as shown by van der Geest et al because being in a wheelchair does not prohibit upper limb activity. In addition, although the 6MWT is a reliable measure with strong concurrent validity, its reliability decreases in advanced (ie, less ambulatory) disease .…”
mentioning
confidence: 99%
“…We are excited to see the use of wearable sensors to measure upper limb activity migrating to studies of children with Duchenne muscular dystrophy (DMD) in the interesting study by van der Geest and colleagues that appears in this issue. This cross‐sectional study used wrist‐worn accelerometers to measure upper limb activity over a period of 1 to 3 days in the home setting as the participants went about their daily lives.…”
mentioning
confidence: 99%
See 1 more Smart Citation